CARROT DRYING TECHNOLOGY - Sirojiddinov Asliddin Abduvahidjon ugli; Zafarova Nozimakhon Khushyorjon qizi (Scholar Express Journal, 2022)
Carrots have a rich chemical composition, due to which they can have a regulatory effect on the metabolism in the human body. Carrots contain proteins and carbohydrates. The content of carbohydrates increases depending on the degree of ripening of the root crop. This vegetable contains little cellulose, so carrots can be used in dietary nutrition. The vegetable is rich in vitamins (B1, B2, B6, C) and minerals (potassium, sodium, calcium, phosphorus, iodine, iron, etc.). It contains a lot of carotene, which is converted into vitamin A in the body
Keywords: Carrot; minerals; method; quality